2014
DOI: 10.12693/aphyspola.125.473
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Mechanical Properties of Metal Inert Gas-Brazed TRIP800 Steel Joints Using Different Shielding Gas Flow Rate

Abstract: In this study, TRIP 800 (transformation induced plasticity) steel plates having 1.5 mm thickness were joined by copper-based (CuAl8) wire in gas metal arc brazing technique. Specimens were prepared in joining forms as butt joint. Brazing operations were done with ve dierent shielding gas ow rates of 8, 10, 12, 14, and 16 L/min. CuAl8 wire composed mostly of copper serves as the ller metal. Having accomplished the brazing operations, tensile properties of joints were detected, and micro-and macrostructures of j… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 11 publications
(9 reference statements)
1
2
0
Order By: Relevance
“…During the arc brazing process, it was observed that the number of dendrites increased on the surface of the joint zone with the increase of current intensity and these dendrites caused micro iron particles to melt and migrate, and to become distributed throughout the ller metal zone. The dendritic structure of the brazed metal in this study is similar with the studies of Chovet [10], Varol et al [11] and Akkas et al [12].…”
Section: Macro and Microstructuressupporting
confidence: 90%
“…During the arc brazing process, it was observed that the number of dendrites increased on the surface of the joint zone with the increase of current intensity and these dendrites caused micro iron particles to melt and migrate, and to become distributed throughout the ller metal zone. The dendritic structure of the brazed metal in this study is similar with the studies of Chovet [10], Varol et al [11] and Akkas et al [12].…”
Section: Macro and Microstructuressupporting
confidence: 90%
“…There is an interface layer between the base metal and braze zone. This white, narrow layer is mainly composed of iron, copper and other alloying elements, present in the ller wire, as mentioned by Akkas et al [12]. In addition, martensite needles can be easily detected in base metal region.…”
Section: Microstructurementioning
confidence: 85%
“…2, c) because the disperse inclusions in the weld joint are intermetallic phase Fe х Al у forms. They have high physical-mechanical features which are much higher than the silicon phases of ferrite [14], and have two times higher volume concentration in the weld joint metal that makes dispersive strengthening more effective [15]. The diffusion zone of those joints is characterized by a more disperse and uniform microstructure.…”
Section: Resultsmentioning
confidence: 99%